TRAVEL BLOG SEBAGAI MEDIA PROMOSI TEBING KERATON DI BANDUNG - Vieka Septilaga; Nani Nurani Muksin (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
The phenomenon of the emergence of Blogs in addition to being used as a medium of information as well as a media  campaign.  For example,  Travel-blog that promotes the Tebing Keraton so that the readers will be interested to visit the Tebing Keraton in Bandung. This study aims to determine the meaning of content of the Travel-blog Cliff Palace; the  meaning of images or visual content; and typography of Travel-blog as a  media promotion of Tebing Keraton. This research use qualitative approach with semiotics research method from Roland Barthes. Sources of  information in this study are three Travel-blogs are: www.pergidulu.com; www.satyawinnie.com and www.cokysihombing.com. Data taken from the  screenshoot  of  each  Travel-blog. The results of this study indicate that: the meaning of the text content of each Travel-blog is almost entirely the same, ie Tebing Keraton has a natural beauty that can make the visitors amazed. Meanwhile, the visual or image content of each blog confirmed the image of the beauty of the Tebing Keraton by showing the green trees, fog, clouds and radiant rays from the rising sun. The thing that distinguished these three blogs is how to write each story, the use of sentences and language, and the typeface.Keywords:  travel-blog, media, promotion, Tebing Keraton.